Cannabis-Based Medicine for Neuropathic Pain and Spasticity-A Multicenter, Randomized, Double-Blinded, Placebo-Controlled Trial - Julie Schjødtz Hansen; Stefan Gustavsen; Homayoun Roshanisefat; Matthias Kant; Fin Biering-Sørensen; Claus Andersen; Anna Olsson; Helene Højsgaard Chow; Nasrin Asgari; Julie Richter Hansen; Helle Hvilsted Nielsen; Rikke Middelhede Hansen; et al. (MDPI AG, 2023)
Patients with multiple sclerosis (MS) and spinal cord injury (SCI) commonly sustain central neuropathic pain (NP) and spasticity. Despite a lack of consistent evidence, cannabis-based medicine (CBM) has been suggested as a supplement treatment. We aimed to investigate the effect of CBM on NP and spasticity in patients with MS or SCI. We performed a randomized, double-blinded, placebo-controlled trial in Denmark. Patients aged ≥18 years with NP (intensity >3, ≤9 on a numerical rating scale (NRS0-10) and/or spasticity (>3 on NRS0-10) were randomized to treatment consisting of either delta-9-tetrahydrocannabinol (THC), cannabidiol (CBD), a combination of THC&CBD in maximum doses of 22.5 mg, 45 mg and 22.5/45 mg per day, respectively, or placebo. A baseline registration was performed before randomization. Treatment duration was six weeks followed by a one-week phaseout. Primary endpoints were the intensity of patient-reported NP and/or spasticity. Between February 2019 and December 2021, 134 patients were randomized (MS n = 119, SCI n = 15), where 32 were assigned to THC, 31 to CBD, 31 to THC&CBD, and 40 to placebo. No significant difference was found for: mean pain intensity (THC 0.42 (−0.54-1.38), CBD 0.45 (−0.47-1.38) and THC&CBD 0.16 (−0.75-1.08)), mean spasticity intensity (THC 0.24 (−0.67-1.45), CBD 0.46 (−0.74-1.65), and THC&CBD 0.10 (−1.18-1.39), secondary outcomes (patient global impression of change and quality of life), or any tertiary outcomes. We aimed to include 448 patients in the trial; however, due to COVID-19 and recruitment challenges, fewer were included. Nevertheless, in this four-arm parallel trial, no effect was found between placebo and active treatment with THC or CBD alone or in combination on NP or spasticity in patients with either MS or SCI. The trial was registered with the EU Clinical Trials Register EudraCT (2018-002315-98).